A field study to isolate bacterial pathogens from otitis media - Miftah Sead Najem; Samia M Al-Ojali; Zuhour Ahseen Amabrouk (Aljameai, 2023)
Abstract:Otitis media is an inflammation of the middle ear and has a worldwide distribution, particularly among children. A total of 68 patients between the ages of 1-42 years who presented with signs and symptoms of otitis media The study was conducted at the Poly Clinic in Ajdabyia City. Samples were transported to the microbiology lab in Aben Naphaes Lab. Middle ear discharge was collected, processed, and bacterial isolates identified using standard microbiological techniques. Disc susceptibility tests were performed on bacterial isolates. Results indicated that there was a high frequency of occurrence of bacteria incriminated in otitis media in the 1–5 and 6–11 year age groups in both sexes. Male patients in the two age groups were more infected than their female counterparts. The sensitivity pattern obtained in this study shows a progressive increase in the emergence of strains that are resistant to many chemotherapeutic agents. Drug resistance among bacterial isolates is a common phenomenon that poses a challenge to both medical practitioners and genetic scientists. A routine check on sensitivity patterns among these pathogens is vital to regulating the prescription measures to be employed. We recommend, according to the result of this study that after swimming or bathing, dry the external canal with a blow dryer on a low setting or by instillation of acidifying or alcohol drops, and avoid overzealous cleansing and scratching (trauma) of the ear.المستخلص:التهاب الأذن الوسطى هو التهاب يصيب الأذن الوسطى وله انتشار عالمي، خاصة بين الأطفال. ما مجموعه 68 مريضا تتراوح أعمارهم بين 1-42 سنة ظهرت عليهم علامات وأعراض التهاب الأذن الوسطى. أجريت الدراسة في إحدى العيادات المجمعة بمدينة اجدابيا. تم نقل العينات إلى مختبر الأحياء الدقيقة في مختبر ابن النفيس. تم جمع إفرازات الأذن الوسطى ومعالجتها وتحديد العزلات البكتيرية باستخدام التقنيات الميكروبيولوجية القياسية. تم إجراء اختبارات حساسية المضادات الحيوية بطريقة الاقراص على العزلات البكتيرية. أشارت النتائج إلى وجود تواتر عال لحدوث البكتيريا التهاب الأذن الوسطى في الفئتين العمريتين 1-5 و 6-11 سنة في الجنسين. كان المرضى الذكور في الفئتين العمريتين أكثر إصابة من نظرائهم من الإناث. يظهر نمط الحساسية للمضادات الحيوية الذي تم الحصول عليه في هذه الدراسة زيادة تدريجية في ظهور سلالات مقاومة للعديد من عوامل العلاج الكيميائي. مقاومة الأدوية بين العزلات البكتيرية هي ظاهرة شائعةتعد مقاومة الأدوية بين العزلات البكتيرية ظاهرة شائعة تشكل تحديا لكل من الممارسين الطبيين وعلماء الوراثة. يعد الفحص الروتيني لأنماط الحساسية بين مسببات الأمراض هذه أمرا حيويا لتنظيم مقياس الوصفة الطبية الذي سيتم استخدامه. نوصي وفقا لنتيجة هذه الدراسة أنه بعد السباحة أو الاستحمام، قم بتجفيف القناة الخارجية باستخدام مجفف شعر على درجة حرارة منخفضة أو عن طريق تقطير قطرات الحمض أو الكحول كذلك تجنب التطهير المفرط والخدش (تلف) لقناة الأذن